Exploring nursing experience of recognising and preventing dehydration amongst the hospitalised elderly population - Dove, Alayna (2014)
Abstract Dehydration has been identified as an avoidable but increasing health condition which greatly increases an individual’s susceptibility to further health concerns. This risk is particularly heightened in the hospitalised elderly population who are increasingly susceptible to dehydration. Within the hospital setting, the nurse has been identified as best placed to recognise and prevent dehydration. A significant gap within the research has been recognised which considers nursing perceptions of dehydration. This dissertation therefore has been undertaken to explore nursing experiences of recognising and preventing dehydration amongst the hospitalised elderly population. In order to achieve this, eight nurses have been interviewed from two healthcare of the older person wards using a hermeneutic phenomenological approach. Each participant has been asked the question ‘what is your experience of recognising and preventing dehydration in elderly inpatients?’ Following this, only prompts have been used to encourage further clarification, exploration or illustration. Upon completion, each interview has been transcribed and this data analysed to develop seven common themes of the research; nursing observations, predisposing factors, the role of the multi-disciplinary team, consideration of the patients view, documentation, interaction with patients and relatives, time available, staffing and training. These themes have enabled me to return to the aim and objectives of this research in order to discuss my findings in relation to the current literature available on the topic of dehydration. The main finding returned from this study has been that the recognition and prevention of dehydration is often viewed as an aspect of basic patient care which my research has demonstrated can often be delivered to patients in an impersonal and task-orientated manner. This study has concluded that the collaboration of the multi-disciplinary team, nursing staffing levels and nursing education all affect how successfully dehydration is recognised and prevented amongst our elderly hospitalised population. It has further suggested that researchers should contemplate qualitative research methods more often when considering the phenomena of dehydration.